Highly effective treatment response and well tolerability by all oral direct acting antivirals for chronic hepatitis C patients post organ transplantation. Issue 1 (January 2020) - Wu, Sih-Hsien; Loong, Che-Chuan; Chu, Chi-Jen; Su, Chien-Wei; Lin, Chung-Chi; Hsia, Cheng-Yuan; Liu, Chinsu; Lee, Shou-Dong; Wang, Yuan-Jen; Lee, Fa-Yauh; Linb, Niang-Cheng; Chen, Cheng-Yen; et al.
Abstract : Background: Immunosuppressant-related acceleration of fibrosis has been documented in chronic hepatitis C (CHC) patients who receive organ transplantation (Tx), and sustained virological response (SVR) rates for these patients by pegylated interferon (IFN)-based therapy are generally poor and associated with unfavorable safety profiles. In addition, IFN treatment varies by patient and poses a high risk of post-renal Tx graft rejection. This study was aimed to investigate the efficacy and safety of all oral direct acting antivirals (DAAs) for CHC patients following organ Tx. Methods: A total of 32 organ Tx (liver: 17, kidney: 13, kidney then liver: 1, and heart: 1) patients with CHC on an oral DAA (paritaprevir/ritonavir, ombitasvir, and dasabuvir: 11, daclatasvir and asunaprevir: 4, sofosbuvir-based: 17) were enrolled in the study. DAAs regimen was based by genotype/subtype, patient characteristics, drug interaction profiles, and health insurance coverage. Results: Mean patient age was 61.4 ± 9.5 years, 50.0% male, and 15.6% with cirrhosis. Fourteen (43.7%) patients experienced unsuccessful IFN treatment. Genotype distribution was as follows: 1a: 6, 1b: 17, 2: 7, 3: 1, and 6: 1. Mean time between Tx and DAAs therapy was 77.3 ± 11.0 months. Baseline HCV RNA before DAAs was 6.20 ± 0.19 log10 IU/mL. After DAAs, the distribution of week 2 HCV RNA was as follows: <15 IU/mL (53.1%), 15 to 50 IU/mL (15.6%), 50 to 100 IU/mL (6.3%), and >100 IU/mL (25.0%), respectively. The rates of undetectable HCV RNA (<15 IU/mL) at week 4 and end-of-treatment were 93.8% and 100%, respectively. Subjective adverse events during therapy were generally mild, with no treatment terminations. After posttreatment follow-up, all 32 patients (100%) achieved SVR12 . Conclusion: Highly responsive treatment and favorable tolerability were achieved by all oral DAAs in this difficult-to-treat patient population.